Current prognostic and predictive biomarkers for gastrointestinal tumors in clinical practice: Review - Fassan, Matteo; Scarpa, Aldo; Remo, Andrea; De Maglio, Giovanna; Troncone, Giancarlo; Marchetti, Antonio; Doglioni, Claudio; Ingravallo, Giuseppe; Perrone, Giuseppe; Parente, Paola; Luchini, Claudio; Mastracci, Luca (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2020)
The pathologist emerged in the personalized medicine era as a central actor in the definition of the most adequate diagnostic and therapeutic algorithms. In the last decade, gastrointestinal oncology has seen a significantly increased clinical request for the integration of novel prognostic and predictive biomarkers in histopathological reports. This request couples with the significant contraction of invasive sampling of the disease, thus conferring to the pathologist the role of governor for both proper pathologic characterization and customized processing of the biospecimens. This overview will focus on the most commonly adopted immunohistochemical and molecular biomarkers in the routine clinical characterization of gastrointestinal neoplasms referring to the most recent published recommendations, guidelines and expert opinions.